The practice of employee learning in SME workplaces: a micro view from the life-cycle perspective. Issue 3 (15th August 2016) - Tam, Steven; Gray, David E
Abstract : Purpose: This study explores how employees in small and medium-sized enterprises (SMEs) practise and view workplace learning at three different life-cycle stages. Design/methodology/approach: It is a qualitative study using a sample of 30 Hong Kong SMEs classified into inception, high-growth or maturity stage, from which firms in each stage were randomly selected and interviewed until data saturation was reached. Snowball sampling was adopted during interviews and data were examined through thematic analysis. Findings: Consistent themes (patterns) from 134 semi-structured interviews are identified, addressing both similarities and differences in the nature of the practice of workplace learning in SMEs between life-cycle stages. Research limitations/implications: More similar comparative studies in other parts of the world, including quantitative surveys on larger samples, with either SMEs or multinational corporations (MNCs), are encouraged to enrich the current findings. Practical implications: If organisational growth is a priority, SME owner/managers should support employees' work and learning in a timely fashion. As the study finds, individual learning and inter-organisational learning are considered "a must to have" for employees, regardless of which stage the firm is at. When an SME enters high-growth, however, more opportunities for group learning are particularly beneficial. For mature SMEs, it is essential for learning to move towards systemisation and include a professional development component to meet employees' career expectations, not just their work demands. Originality/value: The results advance the body of knowledge in SME learning from the life-cycle perspective. As one of the first studies in bridging these areas, it brings new implications to academic researchers and SME practitioners.